2006
DOI: 10.1039/b517888f
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol functionalized dicationic ionic liquids with alkyl or polyfluoroalkyl substituents as high temperature lubricants

Abstract: A series of new polyethylene glycol functionalized dicationic ionic liquids with alkyl or polyfluoroalkyl substitutents (9-17 and 19-24) has been prepared. Important physical properties of these liquids, including glass transition (T g ) and decomposition temperatures (T d ), solubility in common solvents, density (d) and viscosity (g), were measured. These ionic liquids show high thermal stability and good lubricity. In general, imidazolium based dicationic liquids have higher T d (>415 uC) than their triazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 35 publications
8
176
0
5
Order By: Relevance
“…For IL2-di, the COF decreased by 30% with respect to the monocationic IL with alkyl side chains, and by 10% with respect to the monocationic IL with a methoxy PEG side chain. These results are in line with literature [14,36,46].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…For IL2-di, the COF decreased by 30% with respect to the monocationic IL with alkyl side chains, and by 10% with respect to the monocationic IL with a methoxy PEG side chain. These results are in line with literature [14,36,46].…”
Section: Resultssupporting
confidence: 94%
“…The structures of the dicationic IL (IL2-di) and its monocationic analogue (IL2), which was used as a benchmark in this study, are shown in Figure 1. connecting chain [28][29][30][31] that was associated with better tribological properties, higher stability, lower toxicity and corrosiveness of the dicationic ILs [14,[31][32][33][34][35][36][37][38][39][40][41]. In the literature, there is a consensus of opinions that the good friction-reduction and wearresistant properties of ILs are owed to their ability to form stable adsorbed layers and protective tribofilms [4,27,[42][43][44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lubricating oils are typically optimized through additive technology and the development of new additives suitable for use with MACs is important in improving their tribological properties. During the last decade, ionic liquids (ILs) have been rapidly developed as new types of lubricant or lubricant additives due to their excellent tribological performance and unique physicochemical properties, which satisfy the requirements of high-performance lubricants [6][7][8][9]. The structures of commonly used IL lubricants or additives are based on bulky asymmetrical cations such as ammonium, phosphonium, pyridinium and imidazolium cations.…”
Section: Introductionmentioning
confidence: 99%